MENINGKATKAN KEMAMPUAN MENULIS PUISI MELALUI PENERAPAN STRATEGI PEMBELAJARAN KONSTRUKTIVIS SISWA KELAS V - Herman Wijaya (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Based on the observations of pre research made in class V MI NW Pancor Kopong, it found the problem that the Indonesian teachers have difficulty in teaching of poem writing. The problems of low ability to write poetry on students are always a constraint among learners and teachers, especially in V MI NW Pancor Kopong in 2013/2014 academic year. Based on this reality, the researcher conducted a study with the aim to improve students' writing poetry at class V MI NW Pancor Kopomg in 2013/2014 academic year through the implementation of constructivism strategies in learning the Indonesian language. Data collection techniques of this study are test and observation. The collected data were analyzed to find the average value, ideal capabilities and look for the ability of group. Based on the result of analysis, it obtains the outcome of student learning with an average 49.86. Classically, it just reaches 17:24%. It means that of 29 students, there are 6 students who have completed or received value above 65 and an increase in cycle II. At the second cycle, 9 of 29 students have fulfilled the criteria of minimum completeness. Based on the percentage calculation obtained, the classical learning completeness is 31.03%. The result of the second cycle has not yet reached the target set. Target can be reached at the third cycle in which 27 students of 29 or 93.10% have been completed. Result of the third cycle has exceeded the target of 90%. Based on the analysis, the application of constructivism learning strategy models to improve the ability to write poetry in grade V MI NW Pancor Kopong at the academic year 2013/2014 in the field of the Indonesian language is successful. Keywords: Ability to write poetry, constructivism learning strategies.